Combined Papillectomy and Autologous Conjunctival Membrane Graft as Management of Giant Papillae for Severe, Refractory Palpebral Vernal Keratoconjunctivitis—A Case Report - Devina Nur Annisa; Hernawita Suharko; Hasiana Lumban Gaol; Viona Viona (Case Reports in Ophthalmological Medicine)
Conclusion: The management of VKC necessitates a comprehensive approach involving preventive measures, pharmacological treatment, and surgical interventions for refractory cases. This case highlights the potential benefits of surgical techniques, such as papillectomy and autologous conjunctival membrane graft, in managing severe and refractory VKC cases with a history of previous surgical procedure failure. However, it is essential to recognize that exposure avoidance and allergic control remain fundamental in VKC management. Further research and larger studies are required to validate the efficacy of these surgical techniques in managing VKC.